Teachers' Efforts to Overcome Bullying Cases in the School Environment: Effective Steps to Curb Bullying Behavior - Hulkin, Muhammad; Irawan, M. Ferry; Noptario, Noptario; Zakaria, Abd Razak (LPPI Yayasan Almahmudi bin Dahlan, 2024)
The role of teachers is very important in stemming bullying cases in the school environment. This study aims to investigate the efforts made by teachers in overcoming bullying cases in the school environment. Through a descriptive qualitative approach and in-depth interviews via Whatsapp, this research was conducted at Fathona Pakjo Integrated Islamic School Palembang. The research findings show that teachers who successfully address bullying cases have taken effective steps, such as identification of bullying cases using clear indicators, implementation of anti-bullying programs involving students and school staff, and collaboration with other parties such as parents and authorities. The results of this study have important implications in fostering an understanding of teachers' efforts in addressing bullying cases in the school environment, and can serve as a reference for schools and teachers in developing effective strategies to prevent and address bullying, with the aim of creating a safe and supportive learning environment for all students. Important implications include more targeted teacher training and the development of student education programs on empathy and inclusiveness for more effective anti-bullying policies. This conclusion is expected to encourage further research and assist schools in formulating more comprehensive strategies in addressing bullying issues.